Um estudo sobre sofrimento/adoecimento das(os) trabalhadoras(es) do Sistema Único de Assistência Social de Belo Horizonte - Lucinéa Almeida de Amorim (2019)
The new forms of work management can create ambiguities in their organization and exert profound influences on the workers' suffering / illness. They may prevent the subject from exercising control over his activity by dissociating him from his own gesture / act at work. The aim of this study is to analyze the relationship between work and mental suffering / illness in the context of the Sistema Único de Assistência Social of Belo Horizonte. The methodology chosen is qualitative and data collection was performed through focus groups and the use of a field diary. Two focus groups were formed, composed of higher level employees with training in Psychology and Social Work. The method of content analysis of Bardin was adopted having as theoretical reference the Psychodynamics of Work, in dialogue with the Clinic of Activity and Psychosociology. It is evident in this study that the management model adopted, due to the ambiguities presented, has caused discomfort at work, triggering damage to the mental health of employees. Manifestation of symptoms such as anxiety, dissatisfaction, anguish, frustration, sleep disturbance, loneliness, indignity, uselessness, devaluation and weariness are observed. It is noted that the defensive strategies used by workers do not effectively contribute to the transformation of work. Psychic illness proves to be worrying and is expressed by the use of psychiatric medication and the granting of medical licenses to the workers in question. It is considered the importance of developing collective intervention actions aimed at the transformation of work conditions and organization, as well as the implementation of a Municipal Health Policy for Public Servants in the municipality.